Leader’s Machiavellianism and employees’ counterproductive work behavior: testing a moderated mediation model - Cai, Han; Wang, Le; Jin, Xiu (Frontiers in Psychology, 2024)
Counterproductive work behavior wastes organizational resources and significantly damages organizational development. The importance of employees' counterproductive work behaviors in organizations is becoming increasingly obvious. This is directly related to the sustainable development and survival of organizations. This study believes that employees' behavior are closely related to leadership style. In particular, employees' in small-and medium-sized enterprises are often manipulated and deceived by leaders, resulting in dissatisfaction and counterproductive work behavior. In order to address this behavior, this study collected survey data from 289 employees from Chinese SMEs to explore the relationship between perceived abusive supervision and organizational political behavior in machiavellian leadership and counterproductive work behavior. The results suggest that machiavellian positive influence counterproductive work behavior through a mediating role of perceived abusive supervision. Furthermore, leader organizational political behavior moderates the indirect effect of perceived abusive supervision such that the effect is stronger when leader organizational political behavior is high. This study aimed to identify the variables that increase employees counterproductive work behavior, propose recommendations for reducing employees' counterproductive work behavior, expanded the scope of counterproductive work behavior research, and provided a theoretical basis for related studies.